Adiponectin modulates NK‐cell function. Issue 4 (1st March 2013) - Wilk, Sabrina; Jenke, Alexander; Stehr, Jenny; Yang, Chin‐An; Bauer, Sandra; Göldner, Katrin; Kotsch, Katja; Volk, Hans‐Dieter; Poller, Wolfgang; Schultheiss, Heinz‐Peter; Skurk, Carsten; Scheibenbogen, Carmen
<x xml:space="preserve">Abstract</x> Adiponectin (APN) has been shown to exert antiinflammatory effects in various disease models but little is known concerning its regulation of NK‐cell function. Here, we show that the majority of human CD56dim NK cells express surface Adiponectin receptor (AdipoR) 1 and 2 while most CD56high NK cells are AdipoR‐negative. Toll‐like receptor (TLR) ligand‐induced IFN‐γ production was diminished by APN while it had no influence on NK‐cell cytotoxicity. In contrast only a small subpopulation of murine NK cells expresses surface AdipoRs, but about 90% store them intracellularly. APN‐deficient knockout (KO) mice had elevated frequencies of NK cells. However, cytotoxic degranulation of NK cells was decreased in APN knockout (APN‐KO) animals. Accordingly, frequencies of CD11bhighCD27high and CD94high effector NK cells and expression of NKG2D were lower in APN‐KO mice. Upon CVB3 infection NK‐cell function was restored in APN‐KO mice. Our data suggest that in addition to its antiinflammatory effects APN also influences the numerical and differentiation status of NK cells, which may further impact the outcome of immune‐mediated diseases in APN‐KO mice.